Estimasi Pengaruh Vaksin DPT pada Kematian Anak: Analisis Multivariabel data Survailan Demografi dan Kesehatan di Kabupaten Purworejo - Siswanto Agus Wilopo (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Recent controversial reports suggest that recipients of one dose of DTP vaccines had higher mortality than children who had received no DTP vaccine. We reanalyzed data on vaccination and child survival collected from demographic and health surveillance to challenge previous findings.Objectives: To estimate specific and non-specific effects of DTP vaccination on child mortality age 1-24 months under routine vaccination program in Indonesia.Methods: A longitudinal surveillance data provided information on 5647 children below 24 months of age who received DTP and other vaccinations. The main outcome measure was all-cause mortality. Background factors associated with mortality were collected, such as: sex, birth order, dead sibling, mother’s education and family size. We assessed DTP vaccinations as an independent factor with other variables in Cox’s regression models with time dependent covariates.Results: There is no sex differential of mortality among children in Purworejo even after considering other factors using Cox regression analysis. Mortality was lower in the group vaccinated with DTP vaccine compared with those not vaccinated, the relative risk of mortality (RR) being 0.56 with 95% confidence interval (CI) is 0.453–0.690. After controlling for the background factors, recipient of DPT vaccines continued to have a lower mortality with RR=0.74 (95% CI: 0.586–0.925). BCG and measles vaccines have stronger non-specific effects compared to effects of DTP vaccines.Conclusion: Through specific effect against targeted diseases and a non-specific benefit against others illnesses, the study showed reduced mortality among children who received DTP vaccine. There is no reason to change current vaccination policy because DTP was not associated with any harmful effect among girls.Keywords: non-specific effects, DTP Vaccine, child survival, Cox’s Regression